High Risk Conditions and Vaccination Gaps in Invasive Pneumococcal Disease Cases in Tennessee, 2011-2016 - Reed, Victoria Kinley (My University, 2017)
During my four months with the Tennessee Emerging Infections Program (EIP), I was able to consistently grow and apply my knowledge of public health. Vanderbilt University Medical Center was an exceptional place to carry out my Master of Public Health field experience. I was not only exposed to public health in the areas of epidemiology and surveillance, but I also gained valuable experience regarding public health activities performed within a hospital setting. The Infectious Disease physicians, the Emerging Infections Program staff, and all of the Health Policy staff members and students were beyond supportive during my time at Vanderbilt. Through my field experience and my capstone project, I was able to learn specific surveillance methods, extract patient information from medical charts and forms, navigate through pertinent databases, and properly gain informed consent from patients. I completed a primary project and several minor projects during my time at Vanderbilt. My minor projects consisted of data entry for the surveillance of non-invasive pneumococcal pneumonia (SNiPP) study, data cleaning/auditing for the pneumococcal carriage study, and additional tasks with each team in EIP. My capstone project involved the gram-positive bacterium Streptococcus pneumoniae. This pathogen, also known as pneumococcus, causes acute bacterial infections and can easily become life threatening. During this project, I extracted medical information from medical records and databases to conduct a descriptive statistic analysis on Streptococcus pneumoniae. The purpose of my project was to evaluate cases of invasive disease, and to investigate underlying conditions and populations that had invasive pneumococcal disease (IPD) due to lack of vaccination.
Keywords: SNiPP; pneumococcal carriage study